Characterization of CVD Heavily B‐Doped Diamond Thin Films for Multi Electrode Array Biosensors. Issue 11 (2nd November 2017) - Pippione, Giulia; Olivero, Paolo; Fischer, Martin; Schreck, Matthias; Pasquarelli, Alberto
Abstract : Nanocrystalline diamond is an excellent material for the fabrication of Multi Electrode Arrays used to monitor the activity of biological cells and tissues. Yet, the overall performances in terms of background noise, electrochemical activity and transparency for fluorescence detection, are difficult to optimize. The aim of this study is to obtain an orientative guide on how to reach a good compromise between the competing properties. For this purpose, several samples of diamond films were produced under a variety of synthesis conditions, to be employed in the fabrication of amperometric Multi Electrode Arrays. After the fabrication, the samples were characterized from a structural, electrical, electrochemical and optical point of view in order to find possible correlations with the parameters adopted in their production. Abstract : This study was aimed at optimizing the process parameters for growing nanocrystalline boron doped films to be employed for the fabrication of micro electrode arrays intended for use in the field of life sciences. Of particular relevance are the electrical conductivity and the optical transparency, as they clearly appear in competition with each other.